PIPEs : a guide to private investments in public equity - Dresner, Steven, 1970-; Kim, E. Kurt, 1968- (Bloomberg Press, 2006)
Private investments in public equity (PIPEs) offer a practical financing alternative for companies seeking capital and a unique asset for investors. For practitioners who know how to identify and execute transactions, PIPEs present a growing opportunity.This revised and updated guide presents the views, voices, and invaluable expertise of leading practitioners from all specialties in the field. The book is divided into three parts: ""The Business of PIPEs,"" which provides a historical backdrop and overview; ""Regulatory Landscape and Structural Alternatives,"" which details the legal.